Rola przedsiębiorstw innowacyjnych w regionalnych strategiach innowacji : przykład Dolnośląskiej strategii innowacji - Kwieciński, Leszek; Moszkowicz, Krystyna (The Role of Innovative Enterprises in the Regional Innovation Strategies : Case of the Regional Innovation Strategy of Lower Silesia, 2006)
In the European Union countries regions are active participants in innovation policy creation. On the regional level also the aims of regional policy and innovation policy (research and development policy) are formed. One of the common tools for creation of these two policies are Regional Innovation Strategies (RIS). After accession to the European Union in Poland also formed Regional Innovation Strategies, which now are the base for Regional Innovation Systems. Described systems will be the frame for cooperation of the following structures: local governance, research sector, technology transfer institutions, enterprises (especially SME) and financial sector. Lower Silesia as a one of 16 voivodships is also forming such system. However RIS for Lower Silesia is not a proper base for Regional Innovation Systems development. This article presents the first effects and problems on the field of RIS implementation, especially for the innovative entrepreneurs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 506-514